Developmental and toxicological effects of butylated hydroxytoluene metabolites on zebrafish larvae - Won Noh; Yeong-Jin Kim; Sung-Gil Choi; Jin-Woo Park; Ji-Young An; Jong-Su Seo; Jong-Hwan Kim (Scientific Reports)
Abstract Butylated hydroxytoluene (BHT) is among the most widely used synthetic phenolic antioxidants. However, BHT and its metabolites have been detected in aquatic ecosystems, posing potential risks to aquatic organisms. The present study aimed to investigate the effects of BHT metabolites on embryonic development in zebrafish. To this end, embryos were exposed to BHT metabolites, including 3,5-di-tert-butyl-4 hydroxybenzaldehyde (BHT-CHO), 2,6-di-tert-butyl-4-(hydroxymethyl) phenol (BHT-OH), 3,5-di-tert-butyl-4 hydroxybenzoic acid (BHT-COOH), 2,6-di-tert-butyl-P-benzoquinone (BHT-Q), and 2,6-di-tert-butyl-4-hydroxy-4-methylcyclohexa-2,5-dien-1-one (BHT-quinol), from 1–120 h post-fertilization (hpf). BHT-CHO, -OH, -COOH, -Q, and -quinol were toxic to zebrafish larvae with 96 h LC50 values of > 0.10, 15.85, 4.51, > 1.30, and 3.46 mg/L, respectively. Moreover, the acute toxicity of BHT metabolites to zebrafish larvae was indicated by morphological abnormalities, changes in heart rate, and alterations in locomotory behavior. The results indicated that exposure to BHT-COOH and BHT-OH caused intestinal developmental abnormalities, blood coagulation, tail deformities, and pericardial edema. Exposure to BHT-Q and BHT-quinol resulted in abnormal swim bladder development. Moreover, alterations in heart rate and locomotory behavior were observed in zebrafish larvae exposed to BHT-COOH, BHT-OH, and BHT-quinol. These findings demonstrate that exposure to BHT metabolites significantly affects the early growth and developmental stages of zebrafish larvae.